Population structure, genetic diversity and selection signatures within seven indigenous Pakistani goat populations - Kumar, C.; Song, S.; Dewani, P.; Kumar, M.; Parkash, O.; Ma, Y.; Malhi, K.K.; Yang, N.; Mwacharo, Joram M.; He, X.; Jiang, L. (Wiley, 2018)
Goat farming in Pakistan depends on indigenous breeds that have adapted to specific agro‐ecological conditions. Pakistan has a rich resource of goat breeds, and the genetic diversity of these goat breeds is largely unknown. In this study, genetic diversity and population structure were characterized from seven indigenous goat breeds using the goat 50K SNP chip. The genetic diversity analysis showed that Bugi toori goats have the highest inbreeding level, consistent with the highest linkage disequilibrium, lowest diversity and long run of heterozygosity segments. This indicates that this breed should be prioritized in future conservation activities. The population structure analysis revealed four fairly distinct clusters (including Bugi toori, Bari, Black Tapri and some Kamori) and three other breeds that are seemingly the results of admixture between these or related groups (some Kamori, Pateri, Tapri and White Tapri). The selection signatures were evaluated in each breed. A total of 2508 putative selection signals were reported. The 26 significant windows were identified in more than four breeds, and selection signatures spanned several genes that directly or indirectly influence traits included coat colour variation (KIT), reproduction (BMPR1B, GNRHR, INSL6, JAK2 and EGR4), body size (SOCS2), ear size (MSRB3) and milk composition (ABCG2, SPP1, CSN1S2, CSN2, CSN3 and PROLACTIN).